Chalcogen Bonding Catalysis of a Nitro‐Michael Reaction. Issue 47 (23rd October 2019) - Wonner, Patrick; Dreger, Alexander; Vogel, Lukas; Engelage, Elric; Huber, Stefan M.
Abstract: Chalcogen bonding is the non‐covalent interaction between Lewis acidic chalcogen substituents and Lewis bases. Herein, we present the first application of dicationic tellurium‐based chalcogen bond donors in the nitro‐Michael reaction between trans ‐β‐nitrostyrene and indoles. This also constitutes the first activation of nitro derivatives by chalcogen bonding (and halogen bonding). The catalysts showed rate accelerations of more than a factor of 300 compared to strongly Lewis acidic hydrogen bond donors. Several comparison experiments, titrations, and DFT calculations support a chalcogen‐bonding‐based mode of activation of β‐nitrostyrene. Abstract : Dicationic tellurium‐based chalcogen bond donors were applied as catalysts for the first time in the context of a nitro‐Michael addition reaction. Rate accelerations of more than a factor of 300 were observed compared to hydrogen bonding catalysts. Reference experiments demonstrate that the catalytic activity is based on chalcogen bonding.